Characteristics of soft tissues at the apex of the deformity in patients with kyphoscoliosis with underlying type 1 neurofibromatosis - E. N. Shchurova; E. N. Gorbach; G. N. Filimonova; S. O. Ryabykh; E. N. Ochirova (Нервно-мышечные болезни)
Objective. Evaluation of skin sensitivity and analysis of morphological changes in paravertebral muscles and back skin in kyphoscoliotic deformity projection in patients with type 1 neurofibromatosis (NF-1).Materials and methods. Ten NF-1 patients who underwent surgery to treat kyphoscoliosis were examined. Using an electrical esthesiometer thermal pain sensitivity before the surgery was studied in dermatomes corresponding to the apex of the deformity. Skin and muscle biopsy samples were collected intraoperatively in the projection of the apex of the deformity curve and were subsequently analyzed by light and scanning electron microscopy.Results. Patients with kyphoscoliosis with underlying NF-1 were characterized by abnormal thermal pain sensitivity, pathological structural changes in skin and muscles accompanied by disrupted innervation and blood supply.Discussion. The observed changes may be responsible for lowered postoperative reparative potential of tissues and they must be considered in prevention and prognosis of treatment and rehabilitation efficacy.